Renal involvement in leprosy: evaluation of patients in Turkey - Ozturk, Savas; Ozturk, Tulin; Can, Ilkay (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2017)
Introduction: Renal involvement in leprosy has previously been described in the literature and can include amyloidosis, glomerulonephritis, nephrosclerosis, tubulointerstitial nephritis, and granulomas. Aim: To evaluate renal involvement in Turkish patients with leprosy. Material and methods : In total, 32 patients with lepromatous leprosy but without any co-morbidities and 35 healthy control subjects were evaluated for renal involvement at the Elazig Training and Research Hospital in Turkey. The laboratory tests and radiological results concerning renal function were taken from both the patients’ medical records and from current examinations. Results: The levels of creatinine, urea, and leukocyturia in the lepromatous leprosy patients were significantly higher than in the controls (p < 0.001, p < 0.001; p = 0.001, p < 0.01; p = 0.036, p 0.05). On ultrasonographic examination, the prevalence of renal cortical cysts and renal cortical echogenicity in the leprosy patients was significantly higher than in the controls (p = 0.020, p 0.05). Conclusions : Evaluating the renal function in all leprosy patients is important to detect abnormalities and to prevent renal failure, which remains a potential cause of death in this disease.